evans64
evans64
12-05-2022
Mathematics
contestada
3f–4g=1
6f–6g=5
use the elimination method
Respuesta :
shannonsoh230
shannonsoh230
12-05-2022
3f-4g= 1 —(1)
6f-6g= 5 —(2)
(1)x2:6f-8g= 2 —(1a)
(1a)-(2):(6f-8g)-(6f-6g)= 2-5
6f-8g-6f+6g= -3
-2g= -3
g= 3/2
Substitute g= 3/2 into (1):
3f-4(3/2)=1
3f-6=1
3f=7
f =7/3
Answer Link
VER TODAS LAS RESPUESTAS ( 11+ )
Otras preguntas
What is the approximate circumference of a circle that has a center at (3,1) and passes through the point (3,6)?
F(x) is a function ?????????????????????????????????????
The MOST obvious reason why scientists still refer to viruses as non-living is that they
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!! from Emma by Jane Austen Emma Woodhouse, handsome, clever, and rich, with a comfortable home and happy dispos
LA FIN DU CONCORDE? Je n’ai jamais voyagé en Concorde. Et pourtant, après l’avoir vu pour la première fois en 1973, j’en ai rêvé. A l’époque, les constructeurs
Finish this simile. Use your imagination to complete the description. The horse ran like . . . . .
I go further, and affirm that bills of rights, in the sense and to the extent in which they are contended for, are not only unnecessary in the proposed Constit
Consider the following factor and indicate whether it increases or decreases the equilibrium price of gasoline and the equilibrium quantity of gasoline sold. In
CAN SOMEONE PLEASE HELP ME ANSWER THIS
What is 9 kg in grams